Invited Commentary: Machine Learning in Causal Inference—How Do I Love Thee? Let Me Count the Ways. Issue 8 (6th March 2021) - Balzer, Laura B; Petersen, Maya L
Abstract: In this issue of the Journal, Mooney et al. ( Am J Epidemiol . 2021;190(8):1476–1482) discuss machine learning as a tool for causal research in the style of Internet headlines. Here we comment by adapting famous literary quotations, including the one in our title (from "Sonnet 43" by Elizabeth Barrett Browning ( Sonnets From the Portuguese, Adelaide Hanscom Leeson, 1850)). We emphasize that any use of machine learning to answer causal questions must be founded on a formal framework for both causal and statistical inference. We illustrate the pitfalls that can occur without such a foundation. We conclude with some practical recommendations for integrating machine learning into causal analyses in a principled way and highlight important areas of ongoing work.